Religion as an Unemployment Insurance and the Basis of Support for Public Safety Nets: The Case of Latin America and the Caribbean - Camilo Pecha; Inder Jit Ruprah (Inter-American Development Bank (IDB), 2015)
This paper explores the role of religion in mitigating the degree to which unemployment reduces subjective well-being and it examines its support of social programs. The paper goes beyond existing literature in three ways: It extends existing literature to Latin America and Caribbean countries; it explicitly includes analysis of two confounders (social capital and personal traits) ignored in existing literature; and it moves beyond correlation by using the propensity score method to tease out a causal relation between religion and well-being. We find that religion acts as a buffer: Unemployed religious people are relatively happier than are nonreligious unemployed people. However, in contrast with the existing literature, we find that religious people are relatively more supportive of public social policy.
hdl:11319/6978
Keywords: Z12; I31; J65; D02; 330; life satisfaction; religion; unemployment; insurance